Remote Sensing Land Quality Changes in Arid and Semiarid Environments: A Review - Frank, Thoma D (Annals of Arid Zone, 2016)
Remote sensing methods have developed recently to assist land managers in monitoring the long-term ecological condition of arid and semiarid landscapes This paper reviews previously published research that assesses the impact of land quality changes on imagery collected by Landsat over arid and semiarid environments. A discussion of change detection procedures is provided to demonstrate ways that Landsat can be used to identify land quality changes associated with vegetation productivity and erosion.